Biliary fistula through ,the scar of an old lumbothomy. - Cassinelli, Daniel; Galarraga, José; Lorenzelli, Juan (Cirugía del Uruguay, 1976)
The authors describe a case of biliary fistula of unusual location, on the site of an old lumbothomy, probably secondary to an old hepatic traumatism and to a present choledocal obstruction. They describe the treatment through choledoco-duodenostomy, and the evolution of the biliary fistula and of the patient, who died 18 days later due to an intercurrent disease.